(3Gddi aGVd efis (3OjhGf HGdYGejI GdeUQjIs - (3fGLi, CMeOs ((3GdbGgQIs (3OGQ ZQjH ddfTQ hGdJhRjYs, 2018)
(3de Gcf jhekG GJUhQ Gf GMJQa cJGHI GdTYQ hdcf JLQHJi GdTYQjI Hjf GjOjce cKjQkG MdeJ Gei Gf Jchf di JLQHI TYQjI QMeI Gddg YdjgG acKjQkG eG JZRdJ ajgG HcdeGJ HSjWI GYJHQJgG TYQkG Gdi QhMgG GdWGgQI JLQHJi GdTYQjI GdKGfjI hOjhGfi GdKGfi Gddi aGVd efi Gdi cd THGHfG GdYQHi GdWGeM deSJbHd GaVd GdGed gh fHQGS GdMjGI GMdehG hGLJgOhG agfGc QH jQYGfG heWdY YdjfG Gdi eUQ YTbi GdGhd hGdGNjQ GJefi MjfeG JfJgi QMdJi ai gPg GdOfjG Gf jJRcQ GdfGS Gfi MGhdJ Gf Cchf LRA efgGs
11
Keywords: (3GdCOH GdYQHis; (3GdTYQ GdYQHis